Intradermal acupuncture and nursing management of insomnia in a patient with central retinal artery obstruction (皮内针治疗1例视网膜中央动脉阻塞患者失眠的护理体会) - CHEN Ping (陈平); WANG Na (王娜) (Journal of International Translational Medicine Limited, 2024)
This article summarizes the nursing experience of 1 case of insomnia after central retinal artery occlusion treated with intradermal needle. Based on Traditional Chinese Medicine syndrome differentiation and care, the patient was given intradermal acupuncture treatment, combined with emotional nursing, diet nursing and health education, which effectively relieved the insomnia symptoms and improved the recovery and quality of life of the patient. (本文总结采用皮内针治疗1例视网膜中央动脉阻塞后失眠的护理体会。基于中医辨证施护, 给予患者皮内针治疗, 配合情志护理、饮食护理及健康宣教等护理措施, 有效改善患者失眠症状, 对促进患者眼部疾病的恢复起到积极作用。)